Community-based Evaluation of Health-seeking Behavior of People with Animal Bite Injuries in a District of Sri Lanka - MATIBAG, Gino C.; OBAYASHI, Yoshihide; KUMARASIRI, Pallegoda V. R.; KALUPAHANA, Anil W.; TAMASHIRO, Hiko; D. D. Niranjala De SILVA; DITANGCO, Rossana A.; KAMIGAKI, Taro; DISSANAYAKE, D. R. Anuruddhika; G. S. Panduka De S. GUNAWARDENA; WIJEWARDANA, Thula G.; KANDA, Koji (Kokusai Hoken Iryo (Journal of International Health), 2008)
Introduction Of the 55,000 deaths per year due to rabies, 56% occur in Asia and 44% in Africa. Despite the existence of the national rabies control program in Sri Lanka, rabies is still prevalent, suggesting that animal bite victims may have failed to observe the proper first aid measures and seek immediate medical treatment. The purpose of this study is to describe the health-seeking behavior among animal bite victims of a selected population in Kandy District, Sri Lanka. The influences of subjects’ demographic characteristics to these behaviors were studied. Methods We conducted face-to-face interviews in May 2006 among households with family members having history of animal bite injuries. Data on health-seeking behaviors such as first aid measure application, immediate medical consultation, and completion of post-exposure prophylaxis (PEP) were obtained. The association between behaviors and demographic characteristics were evaluated using Chi-square test or the Fisher’s exact test. Results Of the 6968 sample population, 357 (5.1%) had history of animal bites one year prior to the survey. Most of the subjects performed first aid measures (n=297, 83.2%) and sought medical treatment (n=319, 89.4%) within 24 hours (n=295, 82.6%) of the injury. Only 9.8% (n=35) of the subjects completed the PEP. There was no association between health-seeking behavior and demographic characteristics. Two subjects died having symptoms that resembled rabies without completing the necessary PEP, and two animal specimens were sent for laboratory testing that confirmed one case of feline rabies one year prior to the study. Conclusion In general, the health-seeking behaviors of the subjects were not influenced by their demographic characteristics which may contribute to greater difficulties in controlling rabies. To strengthen the rabies control program, effective education of both the public and health sectors by thorough and adequate wound washing, and strict adherence with the recommended treatment schedule is of paramount importance.